Foreign Aid, Conditionality and Ghost of the Financing Gap : A Forgotten Aspect of the Aid Debate - Ranaweera, Thilak (World Bank, Washington, DC, 2014)
Assessing Aid: What Works, What Doesn't, and Why (The World Bank, 1998) generated a new wave of controversy about foreign aid and policy conditionality that had seen several decades of intense debate. Much of the recent debate has focused on the aid-growth relationship and the role of "good" policies. While a great deal has been said about qualitative aspects of aid effectiveness (that is, fungibility, among other things), little attention has been paid so far to some important quantitative aspects. The author draws attention to this neglected aspect of the aid debate to show that the level of aid requirements of a country is an equally important and integral part of aid and aid effectiveness. The author compares the World Bank/IMF approaches to estimation of external assistance requirements of a country in quantitative terms with an alternative model, the "balance of payments constrained growth model" (based on the Harrod trade multiplier). He finds that the latter model is not a real alternative as it is an incomplete model. More important, he shows that international financial institutions use these quantitative frameworks in a very flexible and pragmatic way to carry on a meaningful policy dialogue with both donors and recipient countries, which has an important bearing on aid effectiveness.